Monitoring and Trend Analysis of Air-Borne Particulate Matter (PM10 and PM2.5) at Major Hot-Spot Areas: Mohakhali and Farmgate in Dhaka City (Journal of Chemical Engineering, 2010)
The objectives of this work were to monitor and quantify the airborne particles (PM10 and PM2.5) and topredict the influence of human and natural activities on their ambient concentrations. Samples of Air-borneParticulate Matter (APM) in the size range 0-2.5 μm (PM2.5) and 0-10 μm (PM10) were collectedsimultaneously using two MiniVol portable air samplers at Mohakhali and Farmgate area in Dhaka city.At Mohakhali effective sampling duration was from May 16 to May 23, 2004 and at Farmgate from June 6to June 13, 2004. Continuous seven day monitoring was carried out to find the effect of meteorology, trafficload and other anthropogenic activities on ambient Particulate Matter (PM) pollution level. Weekday andweekend average traffic number was evaluated by field technicians at both sampling sites. These sites areregarded heavily polluted because of the proximity of major roadways. Daily and weekly averageconcentrations of PM10 and PM2.5 at Mohakhali were found higher than USEPA and Bangladesh 24-hrsaverage guideline values but at Farmgate the concentrations were within the guideline values. Averageproportions of PM2.5 in PM10 were found higher at Farmgate than that at Mohakhali.Journal of Chemical Engineering Vol.ChE 24 2006 61-67